2004
DOI: 10.1207/s15327752jpa8303_14
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Therapeutic Alliance During Psychological Assessment: Patient and Therapist Perspectives Across Treatment

Abstract: We examined the impact of patient- and therapist-rated alliance developed during psychological assessment on the subsequent alliance measured early and late in formal psychotherapy. We hypothesized that a working alliance developed during psychological assessment conducted from a collaborative therapeutic model of assessment (TMA; Finn & Tonsager, 1992, 1997; Fischer, 1994) between the patient and therapist would carry into formal psychotherapy. We also hypothesized that alliance for those patients receiving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 42 publications
3
127
0
3
Order By: Relevance
“…Ackerman, Hilsenroth, Baity, and Blagys (2000) found that when clients at a community clinic took part in a collaborative assessment prior to beginning formal psychotherapy, they were much less likely to ultimately terminate therapy against medical advice than clients who participated in a more traditional, information gathering model of assessment. In addition, the results presented in Ackerman et al's (2000) article, as well as later results from the same study (Hilsenroth, Peters, & Ackerman, 2004), indicated collaborative assessment may be associated with higher levels of client-therapist alliance during subsequent psychotherapy when compared with alliance levels reported by clients who received traditional assessment. Similarly, Hanson, Claiborn, and Kerr (1997) found that college students participating in a brief "interactive" (collaborative) assessment were more likely to rate their sessions "deep" and their counselors as expert, trustworthy, and attractive, than students participating in an assessment that involved unilateral feedback from the assessor.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 81%
See 2 more Smart Citations
“…Ackerman, Hilsenroth, Baity, and Blagys (2000) found that when clients at a community clinic took part in a collaborative assessment prior to beginning formal psychotherapy, they were much less likely to ultimately terminate therapy against medical advice than clients who participated in a more traditional, information gathering model of assessment. In addition, the results presented in Ackerman et al's (2000) article, as well as later results from the same study (Hilsenroth, Peters, & Ackerman, 2004), indicated collaborative assessment may be associated with higher levels of client-therapist alliance during subsequent psychotherapy when compared with alliance levels reported by clients who received traditional assessment. Similarly, Hanson, Claiborn, and Kerr (1997) found that college students participating in a brief "interactive" (collaborative) assessment were more likely to rate their sessions "deep" and their counselors as expert, trustworthy, and attractive, than students participating in an assessment that involved unilateral feedback from the assessor.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 81%
“…To date, all of the empirical research on collaborative and Therapeutic Assessment has focused on individual (Ackerman et al, 2000;Finn & Tonsager, 1992;Hilsenroth et al, 2004;Newman & Greenway, 1997) and family clients (Smith et al, 2009;Tharinger et al, 2009;Tharinger, Finn, Wilkinson, & Schaber, 2007). However, an accumulating body of case material suggests collaborative and Therapeutic Assessment techniques may also be useful for psychologists working with couples, either as a precursor or supplement to traditional couples therapy (Butcher, 1990;Dorr, 1981;Finn, 2007;Richman & Davidoff, 1971).…”
Section: Empirical Research On Collaborative and Therapeutic Assessmementioning
confidence: 99%
See 1 more Smart Citation
“…Early alliance can be determined either at a single session or as a developing process (Hilsenroth, Peters, & Ackerman, 2004).…”
Section: Early Alliance Buildingmentioning
confidence: 99%
“…Hilsenroth, Peters and Ackerman (2004) examined a sample of outpatients and their therapists at the end of the assessment feedback session, early, and late in psychotherapy, aiming at verifying the impact of patient-and-therapist-rated alliance developed during psychological assessment on the subsequent alliance measured early and late in formal psychotherapy. They found that a working alliance developed during psychological assessment between the patient and therapist would carry into formal psychotherapy.…”
mentioning
confidence: 99%